Assessment of effect of fixed orthodontic treatment on gingival health: An observational study - Vasu Kumar; Purushottam Singh; Vishal Kumar Arora; Sukhpreet Kaur; Sahil Sarin; Harmeet Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Prime components of fixed orthodontic treatments decrease the self-cleansing ability of the tongue and the cheeks leading to an increase in production of bacterial plaque. Hence, the present study was undertaken for assessing the effect of fixed orthodontic treatment on gingival health. Materials and Methods: A total of 120 patients who were scheduled orthodontic treatment were enrolled. Complete data records of all the patients were recorded. Intra- and extraoral radiographs were obtained and photographic records were noted in separate pro forma. Complete intraoral examination of all the patients was carried out for recording visible plaque, any inflammation (visible clinically), and gingival recession. Based on the assessment of gingival texture and capillary transparency, analysis of gingival biotype was done. Follow-up records were assessed. Results: The mean visible plaque value before treatment and after treatment was found to be 3.11 and 5.81, respectively. The mean visible inflammation value before treatment and after treatment was found to be 2.89 and 15.43, respectively. The mean gingival recession score value before treatment and after treatment was found to be 0.19 and 0.383, respectively. A significant increase in the visible plaque value, visible inflammation value, and gingival recession score was observed posttreatment. While comparing the gingival biotype, it was seen that in both the maxillary and mandibular arches, there was an increase in the thick gingival biotype while there was a decrease in thin maxillary biotype. Conclusion: There is a significant increase in plaque accumulation, inflammation, and gingival recession following fixed orthodontic treatment. Hence, during the course of orthodontic treatment, regular oral prophylaxis should be done.